Pada Mulanya adalah Aku-Engkau: Menelaah Prinsip Kesetaraan Gender dalam Narasi Kejadian 1-3 - Maria Fransiksa Sihombing; Destri Ayu Natalia Hutauruk (STT HKBP Pematangsiantar, 2024)
Gender equality remains a significant topic of discussion within theological discourse. The creation narrative in Genesis 1-3 has historically been interpreted through androcentric and misogynistic lenses, perpetuating theological views that marginalize women. Such interpretations have been transmitted through centuries, contributing to a theological framework that subordinates women. This study seeks to critically examine these androcentric and misogynistic readings of Genesis 1-3 within the Christian tradition and to offer a narrative reinterpretation that reveals hermeneutical insights supporting gender equality. Utilizing a qualitative research methodology, specifically a literature review, the study demonstrates that the original relationship between man and woman, as depicted in Genesis 1-2, reflects an